Enhanced methane production by granular activated carbon: A review. (15th July 2022) - Xiao, Leilei; Liu, Jian; Senthil Kumar, P.; Zhou, Meng; Yu, Jiafeng; Lichtfouse, Eric
Highlights: Promotion of GAC on CO2 reduction and acetoclastic pathway were both summed. A combined effect was proposed, except for direct interspecies electron transfer. Nano-modification strategies were reviewed to improve anaerobic digestion efficiency. The disadvantages for the use of GAC were proposed. Abstract: Biomethane production by anaerobic digestion is an efficient technology to treat organic waste and produce clean energy. A growing number of studies has attempted to use carbon-based materials to enhance methane production performance. Granular activated carbon (GAC) is commonly used due to its low price and high efficiency. Moreover, the high conductivity of GAC favors direct interspecies electron transfer (DIET) coupled with CO2 reduction to accelerate electromethanogenesis. GAC has also other properties such as porosity, which may influence microbial methanogenesis. But the comprehensive contributions to microbiome function were hardly summarized. Herein, we review the effects of GAC on anaerobic carbon mineralization, with focus on conductivity, adhesion, adsorption, pH buffering, and redox mediation. The findings are also applicable to natural ecosystems, such as soils and sediments. We also discuss modification of GAC by nanomaterials to enhance anaerobic performance. We suggest practical GAC applications in anaerobic digestion and energy conservation.